Undulative induction electron accelerator for the waste and natural water purification systems - Kulish, V.V.; Melnyk, A.C.; Gubanov, I.V. (Вопросы атомной науки и техники, 2001)
The project analysis of Undulative Induction Accelerator (EH-accelerator) for the waste and natural water purification systems is accomplished. It is shown that the use of the four-channel design of induction block and the standard set of auxiliary equipment (developed earlier for the Linear Induction Accelerators - LINACs) allow to construct commercially promising purification systems. A quality analysis of the accelerator is done and the optimal parameters are chosen taking into account the specific sphere of its usage.